The Influence of the Use of Pasco Scientific Teaching Aids Against Learning Outcomes and Scientific Attitudes of University of Flores Physics Study Program Students - An Nisaa Al Mu'min Liu; Ilyas Ilyas (Universitas Muhammadiyah Makassar, 2019)
This study aims to determine the scientific attitudes and learning outcomes of students at physics education study programs by applying Pasco Scientific teaching aids based learning and to determine the effect of the use of post-scientific teaching aids on learning outcomes and scientific attitudes of students of physics education study programs. This research is descriptive quantitative. The sample of this study were physics education students who took 33 mechanics class. Data collection was conducted by using tests of learning outcomes, documentation and questionnaire distribution. The results showed that learning outcomes in mechanics after applying learning based on teaching aids post scientific averaged in 80.091. They are categorized as Good category. Scientific attitude variable averaged in 170.3 and it becomes 85.2 if converted. They are categorized as Good category. For the sig (2-tailed) value for the variable of learning outcomes and scientific attitudes obtained 0,000. It is certainly smaller than 0.05, thus it can be said that H0 is rejected and H1 is accepted. Therefore, it can be stated that the use of post-scientific teaching aids influences scientific attitudes and student learning outcomes. Keywords: Pasco Scientific, Scientific Attitude, Learning Outcomes Penelitian ini bertujuan untuk mengetahui sikap ilmiah dan hasil belajar mekanika mahasiswa program studi pendidikan fisika dengan menerapkan pembelajaran berbasis alat peraga Pasco Scientific dan untuk mengetahui pengaruh penggunaan alat peraga pasco scientific terhadap hasil belajar dan sikap ilmiah mahasiswa program studi pendidikan fisika. Penelitian ini merupakan penelitian deskriptif kuantitatif. Sampel dalam penelitian ini adalah mahasiswa pendidikan fisika yang memprogram mata kuliah mekanika sebanyak 33 orang. Pengumpulan data yang dilakukan dalam penelitian ini menggunakan tes hasil belajar, dokumentasi dan penyebaran angket. Hasil penelitian menunjukan hasil belajar mekanika setelah menerapkan pembelajaran berbasis alat peraga pasco scientific rerata 80,091. Jika dikategorikan menurut pedoman penilaian acuan patokan termasuk dalam kategori Baik. Untuk variabel sikap ilmiah mahasiswa dengan rerata 170,3 yang jika dikonversikan dalam nilai menjadi 85,2. Jika dikategorikan menurut Pedoman Penilaian Acuan Patokan termasuk dalam kategori Baik. Untuk nilai sig (2-tailed) untuk variabel hasil belajar dan sikap ilmiah diperoleh 0,000 yang tentu lebih kecil dari 0,05 maka dapat dikatakan H0 ditolak dan H1 diterima artinya penggunaan alat peraga pasco scientific berpengaruh terhadap sikap ilmiah dan hasil belajar mahasiswa program studi pendidikan fisika.Kata kunci: Pasco Scientific, Sikap Ilmiah, Hasil Belajar